Hubungan Tingkat Pengetahuan dan Sikap Masyarakat Tentang Penggunaan Antibiotik di Kelurahan Megang Kota Lubuklinggau - Maifitrianti Maifitrianti; Tuti Wiyati; Shinta Ayu Lestari (Journal of Pharmaceutical and Sciences, 2026)
Introduction: The irrational use of antibiotics has become a global concern due to its potential to trigger antimicrobial resistance (AMR). Various factors contribute to inappropriate antibiotic use, among which limited public knowledge about antibiotics plays a significant role. Understanding the relationship between knowledge and attitudes toward antibiotic use is essential for designing effective educational interventions, particularly in communities with limited access to health information. Objective: This study aimed to assess the level of knowledge and attitudes regarding antibiotic use and to analyze the relationship between these two variables among the community in Megang urban village, Lubuklinggau City, Indonesia. Methods: A cross-sectional study was conducted from June to July 2023 involving 300 respondents selected through proportionate stratified random sampling. Data were collected using a validated questionnaire comprising three sections: sociodemographic characteristics (6 items), knowledge (12 items), and attitudes (8 items). Knowledge and attitude scores were categorized based on median values. The relationship between knowledge and attitude was analyzed using the Spearman Rho correlation test. Results: The majority of respondents (63.3%) demonstrated good knowledge regarding antibiotic use, while 50.3% exhibited positive attitudes. Bivariate analysis revealed a significant positive correlation between knowledge and attitude scores (r = 0.481; p < 0.001), indicating a moderate strength of association. This finding suggests that better knowledge is associated with more positive attitudes toward appropriate antibiotic use. Conclusion: A significant positive relationship exists between the level of knowledge and attitudes toward antibiotic use in the study population. These findings underscore the importance of implementing structured educational interventions, particularly at primary healthcare facilities, to enhance both knowledge and attitudinal aspects of antibiotic use, thereby contributing to the prevention of antimicrobial resistance